Predictive factors for transformative learning within ACTEA-related theological institutions in Ethiopia - Alemu, Alemseged K (Carlisle, Cumbria, UK, Langham Creative Projects, 2022)
While most studies on the nature of transformative learning have been conducted from a Western perspective, Dr. Alemseged K. Alemu explores the concept within an African context. Utilizing a mixed-methods approach, he assesses the components of transformative learning as identified by students and faculty at five theological institutions in Ethiopia. His study sheds light on effective educational practices within higher-level institutions, identifying four factors associated with holistic transformation and the role instructional strategy and interpersonal relationships play in fostering those elements. This is an excellent resource for anyone seeking to cultivate an educational culture that does more than simply transmit information but rather shapes leaders, transforms lives, and empowers men and women to go forth and be like Christ.
Keywords: Religious education.-- Ethiopia; Critical pedagogy.-- Ethiopia; Theological seminaries.-- Ethiopia; Transformative learning.-- Ethiopia